Coverage and determinants of second-dose measles vaccination among under-five children in East Africa countries: a systematic review and meta-analysis - Alemu, Tewodros Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie; Mekonen, Enyew Getaneh; Ali, Mohammed Seid; Zegeye, Alebachew Ferede; Wassie, Mulugeta; Kassie, Alemneh Tadesse; Tekeba, Berhan; Gonete, Almaz Tefera (Frontiers in Public Health, 2024)
Background One of the biggest breakthroughs of contemporary medicine is measles vaccination. It is essential for the total elimination of measles. Understanding the magnitude and determinants of effective second-dose measles vaccination coverage is a critical task. Accordingly, we set out to check the best available evidence of the pooled second-dose measles vaccination coverage among under-five children in East Africa. Method We searched electronic databases such as PubMed, Google Scholar, Cochrane, and others. Two reviewers separately carried out the search of the Joanna Briggs Institute, selection of studies, critical appraisal, and data extraction. A third party was involved in resolving the disagreement among the reviewers. Seven studies included in this study, four from Ethiopia, two from Kenya, and one from Tanzania were cross-sectional and published in English language, with publication dates before 29 November 2023. Articles lacking full-text, the intended outcome, and that are not qualitative studies were excluded from the analysis. The Microsoft Excel checklist was used to extract the data and then exported to STATA 11. In addition, I2, Funnel plots, and Egger's test were employed to measure heterogeneity and detect publication bias, respectively. A random effect model was used. Result The meta-analysis includes a total sample size of 4,962 children from seven articles. The pooled prevalence of second-dose measles vaccination among under-five children in East Africa was found to be 32.22% [95% CI; (18.82, 45.63)], and the significant factors were as follows: birth order (1.72; OR = 95% CI: 1.32, 2.23), information about measles-containing second-dose vaccine (MCV 2) (7.39; OR = 95% CI: 5.21, 10.50), mother's marital status (1.47; OR = 95% CI: 1.05, 2.07), complete immunization for other vaccines (2.17; OR = 95% CI: 1.49, 3.17), and distance of vaccination site (3.31; OR = 95% CI: 2.42, 4.53). Conclusion The current study found that pooled prevalence of second-dose measles vaccination coverage among under-five children was still very low. It was also observed that birth order, distance of the vaccination site, complete immunization for other vaccines, mother's marital status, and information about MCV were factors associated with second-dose measles vaccination. These factors imply that there is a need for countries and their partners to act urgently to secure political commitment, expand primary health service and health education, and increase vaccination coverage.